Behavioral Economics in Consumer Decision-Making : Implications for Marketing Strategies (Universitas Kristen Indonesia Toraja, 2023)
This paper explores how insights from behavioral economics can influence consumer decision-making and improve marketing strategies. By analyzing cognitive biases such as loss aversion, anchoring, and social proof, the study highlights practical applications for pricing, promotions, and customer retention. The paper also provides a framework for integrating behavioral insights into digital marketing campaigns for increased engagement and conversion rates.